Mental health issues of Maria I of Portugal and her sisters: the contributions of the Willis family to the development of psychiatry. Issue 3 (September 2013) - Peters, Timothy J; Willis, Clive
Contemporary accounts credit Dr Francis Willis (1718–1807) with facilitating the recovery of King George III from his major episode of acute mania in 1788–9. Subsequently Willis was summoned to Lisbon to advise on the mental health problems of Queen Maria I. This article reports the nature of the illnesses of Maria and her two similarly affected sisters, and uses the program OPCRIT to propose diagnoses of major depressive disorders. The high prevalence of consanguinity and insanity among the Portuguese monarchy and their antecedents probably contributed to their mental health problems. The successive contributions of the Willis family from Thomas Willis (1621–75) to his grand-nephew, Francis Willis (1792–1859), are reviewed; the popular image is somewhat inaccurate and does not highlight their part in the development of psychiatry.